Dysplasia spondyloepiphysaria and patella dislocation: a case followed over 10 years - Memminger, Michael Kurt (Acta Biomedica Atenei Parmensis, 2019)
Dysplasia spondyloepiphysaria means altered form and seizure of the vertebral bones and the epiphyseal bone regions. Pathologies related to this disease are: scoliosis, short stature, eye problems, articular deformities. We report a case of tarda form. The main problem was habitual and later fixed dislocation of both patellae together with valgus deformities of the knees. We describe the surgical procedures to gain reduced patellae and correction of the mechanical axis.